Предмет:
МатематикаАвтор:
kirahanson(a / (√(ab) - b) - √b / (√b - √a)) * (√a - √b) * b / (a + b) =
(a / (√b(√a - √b) + √b / (√a - √b)) * (√a - √b) * b / (a + b) =
(a / (√b(√a - √b) + b / (√b (√a - √b)) ) * (√a - √b) * b / (a + b) =
(a + b) / (√b(√a - √b)) * (√a - √b) * b / (a + b) =
(a + b) / √b * b / (a + b) =
√b
Автор:
vernonДобавить свой ответ
Предмет:
Русский языкАвтор:
blancaqqaqОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
nana0fxhОтветов:
Смотреть
Предмет:
ФизикаАвтор:
rosarior8yoОтветов:
Смотреть